Innovative strategies under changing diabetes barometer in building diabetes registry in Puducherry - Raman, K. V. (Journal of Social Health and Diabetes, 2013)
Diabetes is continuing to be a huge burden in India with more than 60 million people suffering from it. Managing the growing menace of diabetes, we need to establish proper system and strategy in place. Despite a wealth of literature on prevalence, reliable data on the registry of diabetes is lacking in most parts of the world including India. Without such data, the fight against diabetes is being driven in the dark. The current national or state initiatives in the collection of data are incongruent and call for a concerted approach to gather information and track progress. In this prospect, the initiative taken by Government of Puducherry in collaboration with Novo Nordisk Education Foundation is highly innovative as it ensures whole population coverage, introduction of unique identity for each people, automated data processing, and web-based information system along with effective diabetes management.
Keywords: Automated data processing; diabetes; innovative strategy; unique identification